Working hours flexibility and older workers' labor supply - Anne C. Gielen (Institute for the Study of Labor (IZA), 2007)
This paper studies the presence of hours constraints on the UK labor market and its effect on older workers labor supply, both at the extensive and the intensive margin. Using panel data for the period 1991-2004, the results from a competing risks model show that over-employed male workers can freely reduce working hours with their current employer before retiring completely. However, some over-employed women are observed to leave the labor market early due to hours constraints. Despite the fact that more flexibility in hours may increase labor market participation of older women, this paper presents some explorative results which illustrate that increasing working hours flexibility does not seem to increase older workers total labor supply as has often been suggested.
Keywords: 330; Ältere Arbeitskräfte; Arbeitsangebot; Arbeitszeitflexibilisierung; Geschlecht; Altersgrenze; Großbritannien